Data needs for gender analysis in agriculture - Doss, Cheryl (International Food Policy Research Institute, 2013)
To support gender analysis in agriculture, household surveys should be better designed to capture gender-specific control and ownership of agricultural resources such as male-owned, female-owned, and jointly owned assets. This paper offers guidelines on how to improve data collection efforts to ensure that women farmers are interviewed and that their voices are heard.